Book review: Mathieu, Jon: Mount Sacred. A short global history of holy mountains since 1500 - Kreutzmann, Hermann (ERDKUNDE, 2023)
Mathieu, Jon: Mount Sacred. A short global history of holy mountains since 1500. 155 pp. 11 figs. The White Horse Press. Winwick 2023. ISBN 978-1-912186-716, 30 £. eISBN 978-1-912186-72-3, OA ebook. Mathieu, Jon: Mount Sacred. Eine kurze Globalgeschichte der heiligen Berge seit 1500. 192 pp. 11 figs. Böhlau. Wien 2023. ISBN: 978-3-205-21702-2, eISBN: 978-3-205-21703-9, 35 €. The topic of sacred mountains has been fascinating for mountain researchers that had access to varied peaks on different continents and opened up comparative perspectives. Edwin Bernbaum’s (1990) famous book on Sacred mountains of the world was published a generation ago at the same time when Karl Gratzl (1990) edited his book on Die heiligsten Berge der Welt. It was a time when the human sphere of mountain regions attracted more attention by anthropologists, archaeologists and geographers. Embedded in a less prophane approach their descriptive books hinted towards more rigorous studies on indigenous practices and rituals, emphasized the historical rootedness of mountain communities and led to changing appreciations over time on the path to highlighting mountain exceptionalism and its exalted representation of pristine environments. The recent publication of Jon Mathieu’s Mount Sacred is a welcome reflection about how mountains became sacred objects and sanctified entities covering a period of half a millennium. The author, himself an authority on European Alpine history, has been fascinated by global mountain studies earlier on in his seminal work on the ‘third dimension’ (Mathieu 2011). This as well as the present book were simultaneously published in German and English. It is fascinating to read how sacred mountains have been created and imagined, how belief systems and scientific approaches shaped the perception of mountain peaks. The opening two chapters are devoted to an enquiry that is inspired by seminal works on Eurasian studies with a focus on place and position of mountains in structuring human environments, environmental control and scientific approaches. Eight chapters are devoted to selected mountains, among which we find at the beginning Mount Kailash and at the end Uluru. The former has probably gained the highest attention among Western readers and has been further promoted since being popularised as the ‘holiest mountain’ (Tichy 1937) suggesting a hierarchy of sacredness. In contrast, Uluru, formerly known as Ayers Rock in Australia, has been rather neglected in the above-mentioned books, probably because the mountain towers only 350 metres above the surrounding plains. Uluru has gained in popular appreciation and became a symbol in the recently debated treaty for Indigenous Australians. The two cases from China and Korea – Tai Shan and Paektusan/Changbaishan – have been canonized in their respective political contexts. Beginning with ritual importance and a deep historical rootedness they have been instrumentalized for less religious purposes and fixed on the political maps of China and North Korea. Presenting cases from the Christian realm in the European Alps seemed to be more challenging as there were pilgrimage places in villages and valleys, rather than a tradition of attributed sacredness and mountain worship on Alpine peaks and passes. Jon Mathieu entertains the reader with a number of anecdotes and historical turns in placing crosses there and in a subsequent chapter on erecting crosses in Italy and neighbouring countries on places in order to celebrate Catholic Christians’ persistence at the beginning of the 20th century. Here a comparison with the wider Himalayan arc and its manifold iconography and materiality on passes, springs and rivers would have been interesting because of its pilgrimage practices, plentiful stocks and great variety of expression and ritual veneration. The chapter devoted to North America puts the Black Hills where Black Elk and Lakota Sioux used to pray to their ‘six grandfathers’ (Tunkasila Sakpe Paha) into the centre of attention; it is the same place where the conflict about Mount Rushmore with the rock sculptures of four American presidents emerged. Competition about sacred places occurs as well where adventure sports and rock climbing take place in spiritually laden or only respected places and peaks. This applies for North American national parks obviously more than for the East African volcanoes; the latter having become attractive tourism destinations with the Kilimanjaro and victims of myth creation. Marketing of mountains has often contributed to generating legends and stories about alleged sacredness and spiritual capacities of mountains. In this context many more prominent case studies and mountain regions would come to our mind that are not covered or mentioned in this book. Jon Mathieu made his selection in order to investigate the underlying processes of creating Mount Sacred. Jon Mathieu’s approach to unearth the roots of the sacredness of some mountains and telling us revealing stories about influential actors and changing factors over time has resulted in an entertaining and enlightening text that broadens the horizon of mountain veneration. His book is highly recommended to interested members, promotors and curious visitors of mountain communities.